2014
DOI: 10.1073/pnas.1314718111
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine sulfation in the second variable loop (V2) of HIV-1 gp120 stabilizes V2–V3 interaction and modulates neutralization sensitivity

Abstract: Elicitation of broadly neutralizing antibodies is essential for the development of a protective vaccine against HIV-1. However, the native HIV-1 envelope adopts a protected conformation that conceals highly conserved sites of vulnerability from antibody recognition. Although high-definition structures of the monomeric core of the envelope glycoprotein subunit gp120 and, more recently, of a stabilized soluble gp140 trimer have been solved, fundamental aspects related to the conformation and function of the nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 49 publications
3
41
0
Order By: Relevance
“…This possibility is supported by the position of these residues in the liganded trimer, where S306 is located directly in the 17b binding site, while T319 and E322 are within the unresolved portion of the V3 loop (40). These conclusions are consistent with previous work showing that it is possible to trigger V3 loop exposure independently of V1/V2 exposure and that V1/V2 likely acts as a clamp restraining the unliganded trimer in the closed state (42)(43)(44)(45)(46)(47)(48)(49).…”
Section: Discussionsupporting
confidence: 88%
“…This possibility is supported by the position of these residues in the liganded trimer, where S306 is located directly in the 17b binding site, while T319 and E322 are within the unresolved portion of the V3 loop (40). These conclusions are consistent with previous work showing that it is possible to trigger V3 loop exposure independently of V1/V2 exposure and that V1/V2 likely acts as a clamp restraining the unliganded trimer in the closed state (42)(43)(44)(45)(46)(47)(48)(49).…”
Section: Discussionsupporting
confidence: 88%
“…Although some plants have a TPST and can sulfate phytohormones (20), PG9 expressed in N. benthamiana did not contain detectable amounts of sulfotyrosines, indicating that mammalian-type sulfation does not occur naturally in N. benthamiana leaves. Overexpression of the hsTPSTs hsTPST1 and hsTPST2 (18) increased sulfation of recombinantly produced proteins in mammalian cells (6,28). However, expression of full-length hsTPST1 in N. benthamiana did not yield efficient levels of PG9 tyrosine sulfation.…”
Section: Discussionmentioning
confidence: 99%
“…It is of note that tyrosine sulfation also affects the antigenicity of gp120 itself. It has been reported that gp120 from CD4 + T cell-produced virions is more extensively sulfated than cell line-produced gp120 (28) and that V2 needs to be sulfated to stabilize V3. Thus, efficient tyrosine sulfation of gp120 vaccine candidates might be crucial for eliciting a sustained antibody response.…”
Section: Discussionmentioning
confidence: 99%
“…Electron tomography, cryo-electron microscopy, and biochemical studies have shown that the V1V2 domain is localized at the apex of the trimeric HIV-1 Env structures, and therefore at least some of the V1V2 epitopes are accessible to Abs (75,76). V2 loop sequences differ in length, but the majority of amino acids are highly conserved, suggesting conserved structural elements (77).…”
Section: Abs Targeting Variable Loops 1 and 2 (V1v2)mentioning
confidence: 99%